2018
DOI: 10.1021/acsami.8b18827
|View full text |Cite
|
Sign up to set email alerts
|

Printing Poly(p-phenyleneethynylene) PLEDs

Abstract: Gravure printing of functional thin-film layers of side-chain-substituted poly­(para-phenyleneethynylene)­s (PPEs) is reported. Rheological properties of PPEs in combination with the Hansen solubility model allowed the formulation of enhanced single-component inks. Layer evaluation is performed with reflectometric thin-film recordings in an optical setup for laterally resolved large-area investigation using imaging color reflectometry. An organic light-emitting diode in a simple glass/indium tin oxide/poly­(3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…This observation suggested a stronger resistance of seeds of OPE 9 - b -P2VP 56 compared to that of OPE 9 - b -PNIPAM 47 as demonstrated by a larger fraction of surviving seeds. The solubility parameters , of ethanol, PNIPAM, and P2VP are 26.6, 23.5, and 21.3 MPa 1/2 , respectively, which indicated that ethanol is a better solvent for PNIPAM than P2VP. Thus, the lower solubility of OPE 9 - b -P2VP 56 than that of OPE 9 - b -PNIPAM 47 was supposed to lead to a stronger resistance of seed micelles of OPE 9 - b -P2VP 56 toward dissolution upon heating.…”
Section: Resultsmentioning
confidence: 99%
“…This observation suggested a stronger resistance of seeds of OPE 9 - b -P2VP 56 compared to that of OPE 9 - b -PNIPAM 47 as demonstrated by a larger fraction of surviving seeds. The solubility parameters , of ethanol, PNIPAM, and P2VP are 26.6, 23.5, and 21.3 MPa 1/2 , respectively, which indicated that ethanol is a better solvent for PNIPAM than P2VP. Thus, the lower solubility of OPE 9 - b -P2VP 56 than that of OPE 9 - b -PNIPAM 47 was supposed to lead to a stronger resistance of seed micelles of OPE 9 - b -P2VP 56 toward dissolution upon heating.…”
Section: Resultsmentioning
confidence: 99%
“…48,49 The Hansen solubility parameters of OPE, PNIPAM, ethanol and water are 16.7, 23.5, 26.6 and 47.8 MPa 1/2 , respectively. [50][51][52] We then tested the micellar stability of the formed aggregates in ethanol/H 2 O, since it was supposed that the addition of water with a much larger polarity could decrease the solubility, that is the mobility, of OPE 7 -b-PNIPAM and make the formed aggregates freeze. Dispersions of each BCP of OPE 7 -b-PNIPAM 8 , OPE 7 -b-PNIPAM 22 and OPE 7 -b-PNIPAM 47 in ethanol/H 2 O (v/v = 90/10, 10 v/v% of water) were heated at 80 °C for 30 min and then allowed to cool and age at 23 °C for 24 h.…”
Section: Cdsa Behaviors and Micellar Kinetic Stability For Ope 7 -B-p...mentioning
confidence: 99%
“…The Hansen solubility parameters of OPE, PNIPAM, ethanol and water are 16.7, 23.5, 26.6 and 47.8 MPa 1/2 , respectively. [50][51][52] On the basis of these values, the addition of water will result in an increase in the solubility parameter of the mixture and lead to a larger difference in the solubility parameter between OPE 7 -b-PNIPAM 22 and the mixture. Thus, the addition of water will decrease the solubility of OPE 7 -b-PNIPAM 22 in the mixture.…”
Section: Papermentioning
confidence: 99%
“…For instance, PE-based molecular systems have been explored for surface engineering, as elements in optoelectronic systems such as in molecular electronics and for the design of donor-acceptor systems. [54][55][56][57][58][59] However, a systematic understanding of the effect of structural branching and molecular symmetry on the photophysics of this class of molecules is still lacking. In this regard, multibranched systems having two, three, four and six equivalent phenylacetylene branches, arranged to share the same central benzene unit, have been synthesized as shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%